A Report on Penaeid Prawn Diversity in Digha Coast, Bay of Bengal, India - Sanchita Nayak Tripathy; Arun Jana; Godhuli Sit; Angsuman Chanda (Çanakkale Onsekiz Mart University Journal of Marine Sciences and Fisheries)
Prawn community in the coastal habitat of Digha is predominantly composed of the family Penaeidae. The present study evaluates the diversity of Penaeidae species in the Digha coast. Penaeidae species were obtained from the Digha Coast between January 2022 and January 2024. A total of 26 species from 8 genera were documented from the Digha Coast and five species represent the first observation from the study area. The Penaeid prawn diversity in Digha Coast, West Bengal of India is substantial. This study will provide valuable insights for prawn fisheries managers and researchers in the study region.